2016
DOI: 10.1186/s40478-016-0402-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the novel A53E alpha-synuclein mutation on its oligomerization and aggregation

Abstract: α-synuclein (aSyn) is associated with both sporadic and familial forms of Parkinson’s disease (PD), the second most common neurodegenerative disorder after Alzheimer’s disease. In particular, multiplications and point mutations in the gene encoding for aSyn cause familial forms of PD. Moreover, the accumulation of aSyn in Lewy Bodies and Lewy neurites in disorders such as PD, dementia with Lewy bodies, or multiple system atrophy, suggests aSyn misfolding and aggregation plays an important role in these disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 66 publications
(79 reference statements)
11
30
0
Order By: Relevance
“…To investigate how A53E may lead to neurodegeneration, earlier in vitro studies examined its effects on α‐synuclein aggregation properties . They demonstrated that A53E α‐synuclein spends a protracted time in oligomeric forms with delayed β‐sheet‐containing fibril formation compared with WT α‐synuclein.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…To investigate how A53E may lead to neurodegeneration, earlier in vitro studies examined its effects on α‐synuclein aggregation properties . They demonstrated that A53E α‐synuclein spends a protracted time in oligomeric forms with delayed β‐sheet‐containing fibril formation compared with WT α‐synuclein.…”
Section: Resultssupporting
confidence: 86%
“…CD spectra of unphosphorylated A53E demonstrated a random coil conformation on day 7, which remained unchanged after 13 days of incubation. EM revealed only amorphous oligomers; no fibrils formed after prolonged incubation periods of 7 and 13 days, consistent with prior studies . With phosphorylation of A53E, CD spectra consistent with a more β‐sheet conformation was observed after 7 days of incubation, and transition to typical β‐sheet was complete on day 11.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Though the mechanisms are poorly understood, all currently known mutations occur in the N-terminal AMP domain (A53T, G46L, G51A, etc.) and result in an autosomal dominant syndrome resembling sporadic PD [17]. The N-terminal domain also contains four repeats with a mitochondrial targeting signal, potentially underscoring the mitochondrial dysfunction seen in PD [17].…”
Section: Introductionmentioning
confidence: 99%
“…and result in an autosomal dominant syndrome resembling sporadic PD [17]. The N-terminal domain also contains four repeats with a mitochondrial targeting signal, potentially underscoring the mitochondrial dysfunction seen in PD [17]. The second NAC domain is a hydrophobic core strongly associated with α-synuclein aggregation and fibrillization [18].…”
Section: Introductionmentioning
confidence: 99%